Fixed points of multivalued nonlinear F-contractions on complete metric spaces - Altun, Ishak; Mınak, Gülhan; Olgun, Murat (Nonlinear Analysis: Modelling and Control, 2016)
We introduce a new concept for multivalued maps, also called multivalued nonlinear F-contraction, and give a fixed point result. Our result is a proper generalization of some recent fixed point theorems including the famous theorem of Klim and Wardowski [D. Klim, D. Wardowski, Fixed point theorems for set-valued contractions in complete metric spaces, J. Math. Anal. Appl., 334(1):132–139, 2007].
Keywords: fixed point; multivalued maps; nonlinear F-contraction; complete metric space